Catch Efficiency of Cast Nets for Snow Trout Fishing in Dal Lake, Kashmir - Azhar, Mudassir; Edwin, Leela; Manoj Kumar, B.; Thomas, Saly N.; Remesan, M. P. (Fishery Technology, 2020)
Experimental cast net fishing was carried out in the Dal Lake of Kashmir to study the catching efficiency, species wise catch composition and size frequency. In terms of fish caught by numbers, cast net Type II monofilament stringed landed 107 fishes and Type I monofilament stringless landed 104 fishes. Multifilament stringed net caught 65 fishes and multifilament stringless net caught only 64 fishes out of 50 operations of each cast net. Four species of snow trout were caught in experimental operations. During the study the monofilament cast nets were found to have better catching efficiency than the multifilament cast nets.